Extracellular vesicles as an emerging tool for the early detection of Alzheimer's disease. (December 2019) - Li, Tao-Ran; Wang, Xiao-Ni; Sheng, Can; Li, Yu-Xia; Li, Frederic Zhen-Tao; Sun, Yu; Han, Ying
Highlights: Researchers can harvest brain-derived exosomes in blood, this approach can accurately reflect the pathological changes of brain. Exosomes may function as Trojan horses, facilitating the accumulation and spread of AD associated toxic cargos in the brain. By detecting Aβ42 or tau or other biomarkers from brain-derived exosomes in blood, we can advance the diagnosis of AD by 10 years. The diagnostic sensitivity and specificity of AD can reach to 87 % and 77 % respectively by detecting blood-derived exosomal miRNAs. Abstract: Alzheimer's disease (AD) is characterized by a series of interacting pathophysiological cascades, including the aggregation of β-amyloid plaques and the formation of neurofibrillary tangles derived from hyperphosphorylated tau proteins. AD is the cause of approximately 70 % of dementia, an irreversible and untreatable syndrome at its late stage. Hence, more efforts should be devoted to identifying at-risk or preclinical AD populations for early intervention and the improved design of drug trials. The exosome, a nanoscale subtype of extracellular vesicle that serves as a cell-to-cell communication messenger, is an emerging liquid biopsy tool for various diseases including AD. Recently, it has been discovered that brain-derived exosomes can flow through the blood-brain barrier to the peripheral blood, containing important protein and nucleic acid biomarkers that are associated with the pathogenesis and progression of AD. Other reports showed a strong involvement of exosomes in synaptic function, insulin resistance, and neuroinflammation, among others. Here, we summarize those studies and assess the value of exosomes as an emerging tool for the early detection of AD in conjunction with the current clinical diagnosis paradigm.